Relation of bleeding patterns and factor VIII levels in children with hemophilia - Rina Rahardiani; H. S. Moeslichan MZ; Agus Firmansyah (Indonesian Pediatric Society, 2006)
Background The high costs of factor VIII examination cause thedelay in the diagnosis of hemophilia A; consequently many pa-tients do not receive adequate therapy which results in failure tosurvive into adulthood or survive with creeple.Objective To determine bleeding patterns of hemophilia A pa-tients for the prediction of its classification.Methods We perform retrospective analysis of hemophilia patientsat the Integrated Service Center of Hemophilia, Cipto Mangun-kusumo Hospital, Jakarta.Results Family history, age at the first bleeding, frequency of bleed-ing, and factor VIII examination can significantly differentiate theclassification of hemophilia A (P=0.015; 0.014; <0.0001; and<0.0001, respectively) while age groups, triggering trauma for thefirst bleeding, type of the first bleeding, history of previous trauma,the most frequent type of bleeding, age at diagnosis, and con-sumption of cryoprecipitate cannot. (P=0.985; 0.475; 0.342; 0.318;0.058; 0.477; and 0.547, respectively).Conclusion Age at first bleeding, frequency of bleeding, and fam-ily history can be used to predict classification of hemophilia A.